Comparison of Exercise and Eating Between College and Former High School Athletes - Laura L. Blair; Melinda Wells Valliant; Kathy B. Knight; John C. Garner (Shiraz University of Medical Sciences, 2016)
Background: Although college students are more likely to exhibit characteristics of eating disorders than other age groups, results are mixed as to whether college athletes are more at risk for disordered eating than non-athletes or former high school athletes. Objectives: The purpose of this cross-sectional study was to determine if collegiate male and female athletes are more likely to exhibit characteristics of an eating disorders compared to college males and females who participated in high school sports but did not continue playing collegiately. Patients and Methods: A survey consisting of the eating attitude test 26 (EAT-26), the body shape questionnaire (BSQ) and three sections of the eating disorder inventory (EDI) body dissatisfaction (EDIBD), drive for thinness (EDIDFT) and the bulimia (EDIBUL) was administered to collegiate athletes (n = 107), former high school athletes (n = 152), and those who did not play sports in high school (non-athletes) (n = 31) in April and May of 2011. Results: A comparison of collegiate athletes, high school athletes, and non-athletes resulted in ANOVA significant (P ≤ 0.05) for EAT (F = 6.145, P < 0.002), EDIDFT (F = 4.834, P < 0.009), EDIBUL (F = 4.264, P < 0.015), EDIBD (F = 12.734, P < 0.001), and BSQ (F = 10.998, P < 0.001). Conclusions: The results of this study do not support previous findings that athletes are more likely to exhibit characteristics of an eating disorder than non-athletes as athletes scored significantly lower on the EAT, EDIDFT, EDIBD, and BSQ. Although no significant difference was found between high school athletes and non-athletes, high school athletes on average scored lower on all five measures. These results reveal that more research needs to be conducted to determine if one of these groups is at a greater risk of an eating disorder than the other.